PENGARUH KERAGAMAN PRODUK, KUALITAS, DAN KEPUASAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA SHOPEE ONLINE - SUSIANA SIMAMORA; REALIZE . (LP2MTBM MAKARIOZ, 2020)
Shopee is one of the marketplace applications that have features for buying and selling transactions. This online or onlineshop business system is an activity carried out by the seller and buyer by not directly or not face to face but through theinternet by displaying or displaying the products that have been provided. and interested buyers or who visit the website ofthe online store this research aims to find out and explain how the influence of product diversity, quality and customersatisfaction on purchasing decisions. The population in this study is all consumers or people of the sagulung district of BatamCity who have made purchases at Shopee And the sample in this study was 383 people using purposive sampling with thetechnique of taking data by distributing questionnaires and processed through the application of SPSS 22. Data analysisused descriptive analysis and linear regression. Testing was obtained using n t test with 1984 product diversity variable witha significance value of 0.048 <0.05, and the quality variable of 2.887 with a significant value of 0.004 and for customersatisfaction of 5.056 with a significant 0.000 <0.05 and the f test to determine the effect simultaneously obtained F count of56,390 <2.62 in the table, sig value 0,000 <0.05, which means that Ho is rejected and Ha is accepted. Which consists ofproduct diversity, quality and customer satisfaction variables has a significant effect on purchasing decisions at onlineshopee proven to be true.